N‐Palmitoylglycine and other N‐acylamides activate the lipid receptor G2A/GPR132 - James R. Foster; Shohta Ueno; Mao Xiang Chen; Jenni Harvey; Simon J. Dowell; Andrew J. Irving; Andrew J. Brown (Wiley, 2019)
Abstract The G‐protein‐coupled receptor GPR132, also known as G2A, is activated by 9‐hydroxyoctadecadienoic acid (9‐HODE) and other oxidized fatty acids. Other suggested GPR132 agonists including lysophosphatidylcholine (LPC) have not been readily reproduced. Here, we identify N‐acylamides in particular N‐acylglycines, as lipid activators of GPR132 with comparable activity to 9‐HODE. The order‐of‐potency is N‐palmitoylglycine > 9‐HODE ≈ N‐linoleoylglycine > linoleamide > N‐oleoylglycine ≈ N‐stereoylglycine > N‐arachidonoylglycine > N‐docosehexanoylglycine. Physiological concentrations of N‐acylglycines in tissue are sufficient to activate GPR132. N‐linoleoylglycine and 9‐HODE also activate rat and mouse GPR132, despite limited sequence conservation to human. We describe pharmacological tools for GPR132, identified through drug screening. SKF‐95667 is a novel GPR132 agonist. SB‐583831 and SB‐583355 are peptidomimetic molecules containing core amino acids (glycine and phenylalanine, respectively), and structurally related to previously described ligands. A telmisartan analog, GSK1820795A, antagonizes the actions of N‐acylamides at GPR132. The synthetic cannabinoid CP‐55 940 also activates GPR132. Molecular docking to a homology model suggested a site for lipid binding, predicting the acyl side‐chain to extend into the membrane bilayer between TM4 and TM5 of GPR132. Small‐molecule ligands are envisaged to occupy a "classical" site encapsulated in the 7TM bundle. Structure‐directed mutagenesis indicates a critical role for arginine at position 203 in transmembrane domain 5 to mediate GPR132 activation by N‐acylamides. Our data suggest distinct modes of binding for small‐molecule and lipid agonists to the GPR132 receptor. Antagonists, such as those described here, will be vital to understand the physiological role of this long‐studied target.